Measuring Consumer Preferences for Video Content Provision via Cord‐Cutting Behavior. Issue 2 (26th September 2016) - Prince, Jeffrey; Greenstein, Shane
Abstract : The television industry is undergoing a generational shift in structure; however, many demand‐side determinants are still not well understood. We model how consumers choose video content provision among over‐the‐air (OTA), paid subscription to cable or satellite, and online streaming (also known as over‐the‐top, or OTT). We apply our model to a U.S. data set encompassing both the digital switchover for OTA and the emergence of OTT, along with a recession, and use it to analyze cord‐cutting behavior (i.e., dropping of cable/satellite subscriptions). We find high levels of cord cutting during this time, and evidence that it became relatively more prevalent among low‐income and younger households—suggesting this group responded to changes in OTA and streaming options. We find little evidence of households weighing relative content offerings/quality when choosing their means of video provision during the timespan of our data. This last finding has important ramifications for strategic interaction between content providers.